Using PRAAT in Teaching the Monophthongs to the EFL Students in Indonesia - Nurjannah Nurjannah; Miftahul Jannah; Intan Zuhra; Fariza Wati (Scope : Journal of English Language Teaching, 2023)
PRAAT can easily and rapidly improve the students’ ability in pronouncing monophthongs in phonetics class. The effectiveness of this software can help the students acquire quality monophthongs sounds. Furthermore, this software could reduce the problem of students learning sounds of monophthongs accurately such as the accuracy of F1 and F2 that is contained in monophthongs. It provided many programs on how to record, analyze, measure, and save in the wave file. This research aimed to investigate  to what extent this software affects teaching monophthongs sounds in phonetics class for students. This research was conducted with 40 samples of students. They divided the class into 20 students for the control group and another 20 students for the experimental group. This quasi-experimental was to determine the best treatment before and  after giving the treatment by using CALL for the experimental group and NON-CALL for the control group. Before using the software,  the students were given the pre-test . Finally, they  sat for post- test in the last meeting. The result was exposed through analysis of a t-test. It showed a significant difference in learning through PRAAT software (p<.05). In addition to that, teaching vowels sounds proved to be more successful using PRAAT than the traditional method.